Cleavage pattern predicts developmental potential of day 3 human embryos produced by IVF. Issue 6 (June 2015) - Yang, S.T.; Shi, J.X.; Gong, F.; Zhang, S.P.; Lu, C.F.; Tan, K.; Leng, L.Z.; Hao, M.; He, H.; Gu, Y.F.; Lu, G.X.; Lin, G.
Highlights We propose a hierarchical classification model to select day 3 embryos with high potential for development into blastocysts based on the severity and occurrence of abnormal divisions during the initial three embryo cleavages. In a prospective observational study, the efficiency of this classification model was assessed and validated. Cleavage patterns can predict the developmental potential of day 3 human embryos.